RESEAECH OF PARAMETERS OF QUALITY OF DEFINITION OF NETWORK ATTACKS OF THE PROBE CATEGORY WITH USE OF THE SELF ORGANIZING MAP - Пахомова, Вікторія; Павленко, Ілля (SWorldJournal, 2022)
To determine network attacks of the Probe category, Python created the program "SOM_Probe" based on the implementation of Kohonen Self Organizing Map 30*30, the structure of which is 15-5 (where 15 - the number of network traffic input parameters, 5 - th